2022
DOI: 10.1021/acsnano.2c02515
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric Moiré Stripes on the Surface of Bi2Se3 Topological Insulator

Abstract: Mismatch between adjacent atomic layers in low-dimensional materials, generating moiré patterns, has recently emerged as a suitable method to tune electronic properties by inducing strong electron correlations and generating novel phenomena. Beyond graphene, van der Waals structures such as three-dimensional (3D) topological insulators (TIs) appear as ideal candidates for the study of these phenomena due to the weak coupling between layers. Here we discover and investigate the origin of 1D moiré stripes on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the last decade, Bismuth is a pioneer in topologically insulating nanomaterials (TIs), from strong or weak of 3D TI, topological metals TIs, semimetals TIs to magnetic TIs, while retaining the usual layered structural patterns [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Bi 2 Se 3 TI thin films and nanoribbons with 1D Mohr stripe films on the surface, having a strongly enhanced surface density of states TI 1D cloudy superstructure due to weak coupling between the layers, became ideal candidates for van der Waals structures 3D TI [15]; 3D TI of Bi 2 Se 3 nanoribbons due to their very high mobility of surface Dirac states and low bulk carrier density [19]. (Bi, Sb) 2 (Te, Se) 3 TI films, eliminating crystal defects, reducing bulk carrier concentration, tuning the Fermi energy level to the Dirac point, and fabricating TI/superconductor pelletss completely in situ [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, Bismuth is a pioneer in topologically insulating nanomaterials (TIs), from strong or weak of 3D TI, topological metals TIs, semimetals TIs to magnetic TIs, while retaining the usual layered structural patterns [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Bi 2 Se 3 TI thin films and nanoribbons with 1D Mohr stripe films on the surface, having a strongly enhanced surface density of states TI 1D cloudy superstructure due to weak coupling between the layers, became ideal candidates for van der Waals structures 3D TI [15]; 3D TI of Bi 2 Se 3 nanoribbons due to their very high mobility of surface Dirac states and low bulk carrier density [19]. (Bi, Sb) 2 (Te, Se) 3 TI films, eliminating crystal defects, reducing bulk carrier concentration, tuning the Fermi energy level to the Dirac point, and fabricating TI/superconductor pelletss completely in situ [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that ZT of thermoelectric materials typically stays around 1.0 [14][15][16][17][18][19][20]. The conversion efficiency of Bi 2 Te 3 is low, but low power applications are gradually gaining the attention of researchers [21][22][23][24][25][26][27][28]. Currently, a wide range of demands have been developed for low-power generation and cooling technologies, the applications of which primarily operate in room-or low-temperature environments, such as micro-motor power systems, IoT wireless sensing modules, and wearable intelligent samples [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a hydrothermal method has been proven to be a feasible method to change the morphology and size of the synthesized Bi 2 Te 3 nanostructures with low equipment and operating requirements, low cost, and low synthesis temperatures. Considerable effort has shown the synthesis of Bi 2 Te 3 , Bi 2 Se 3 , Sb 2 Te 3 , BiTe, and PbTe nanomaterials by using a solvothermal method [13,[19][20][21][22][23][24][25][26][34][35][36][61][62][63][64]. Some studies reported the effect of the morphology of the products, but the synthesis method was not "green", and some reported that the synthetic method was "green," but the morphological changes were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is possible to achieve one-dimensional (1D) moiré patterns between 2D materials by enforcing a periodic modulation selectively in one direction, as illustrated in Figure a. Different approaches for achieving these moiré patterns have been proposed, including vertical and lateral heterostructures of lattice-mismatch heterostrained materials, nanotubes, , substrate-driven moiré patterns, or chemically functionalized surfaces. However, earlier theoretical and experimental works restrict their focus mainly to the coexistence of the twist angle and accompanying strain in moiré materials, with a detailed understanding of the individual effect and properties of heterostrain currently lacking. In this Letter, we expand the class of moiré materials beyond twisted systems by introducing heterostrained bilayer graphene (hBLG), in which uniaxial strain is exerted in only one of the two layers.…”
mentioning
confidence: 99%